Deradicalization and Formation of Public Attitudes of Islamic Boarding School (Pesantren) in Sukoharjo, Indonesia - arkanudin budiyanto; Subejo Subejo; Samsul Maarif (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2020)
The spread of religious radicalism in Indonesia has pervaded all levels of society without being able to be sorted are rigid. Responding to the situation, the government does the de-radicalization program, included Pesantren. This study aims to identify the communication strategy, internal and external factors in shaping public attitudes of Islamic Boarding School (Pesantren) towards the de-radicalization of religious with quantitative and qualitative approaches. The data collection is done by observation, interviews, questionnaires, and focus group discussions. Quantitative analysis tools using SEM. The results showed that the communication strategy of de-radicalization effect on public attitudes of Islamic Boarding School (Pesantren) through external factors significantly. External factors also influence the public's attitudes of Islamic Boarding School (Pesantren) directly with a strong and significant influence. The communications strategy of de-radicalization also directly affects the public's attitudes of Islamic Boarding School (Pesantren) with weak influence.[Penyebaran radikalisme agama di Indonesia telah merasuki semua lapisan masyarakat tanpa dapat dipilah secara rigid. Merespon situasi tersebut, pemerintah melakukan program deradikalisasi, termasuk di lingkungan Pesantren. Penelitian ini bertujuan untuk mengidentifikasi strategi komunikasi, faktor internal dan eksternal dalam membentuk sikap masyarakat pesantren terhadap deradikalisasi agama dengan pendekatan kuantitatif dan kualitatif. Pengumpulan data dilakukan dengan observasi, wawancara, kuesioner, dan FGD. Alat analisis kuantitatif menggunakan SEM. Hasil penelitian menunjukkan bahwa Strategi komunikasi deradikalisasi berpengaruh terhadap sikap masyarakat pesantren melalui faktor eksternal secara signifikan. Faktor eskternal juga mempengaruhi sikap masyarakat pesantren secara langsung dengan pengaruh yang kuat dan signifikan. Strategi komunikasi deradikalisasi juga berpengaruh langsung terhadap sikap masyarakat pesantren dengan pengaruh yang lemah.]